Participatory digital methodologies: Potential of three approaches for advancing transformative occupation-based research with children and youth. Issue 4 (2nd October 2019) - Benjamin-Thomas, Tanya Elizabeth; Laliberte Rudman, Debbie; Cameron, Debra; Batorowicz, Beata
ABSTRACT: This paper addresses the need for methodological expansions that enable critical examination of the situated nature of occupation and enact transformative research agendas. Participatory digital methodologies offer a potential way forward given their critical underpinnings and have been proposed as particularly appropriate to facilitate engagement of children and youth. This paper provides a critical methodological review of interdisciplinary research with children and youth that has utilized one of three participatory digital methodologies (i.e., digital storytelling, participatory videos and participatory geographic information systems) for transformative research addressing social and health inequities in ways that also attend to occupation. Working with a sample of 20 research articles, analysis focused on critically considering how the examples demonstrated participation of children and youth, enacted transformation, and addressed occupation. All three methodologies demonstrated strengths as participatory methodologies in involving children and youth within research and action processes, although with challenges and tensions related to power sharing. Transformation at the personal level was often claimed, with fewer examples addressing social transformation. Knowledge relevant to the situated nature of occupation, occupational spaces, and occupational injustice emerged. This review demonstrates that participatory digital methodologies offer a promising direction forward in enacting a transformative occupation-based research agenda that involves working with children, youth, and other community members.